Advantages of the robotic approach to deep infiltrating rectal endometriosis: because less is more. Issue 2 (June 2016) - Araujo, Sergio; Seid, Victor; Marques, Renato; Gomes, Mariano
Abstract For symptomatic deep infiltrating endometriosis, surgery is often required to achieve symptom relief and restore fertility. A minimally invasive approach using laparoscopy is considered the gold standard. However, specific limitations of the laparoscopic approach deep in the pelvis keep challenging even surgeons with a solid experience with minimally invasive techniques. Robotic surgery has the potential to compensate for technical drawbacks inherent in conventional laparoscopic surgery, such as limited degree of freedom, two-dimensional vision, and the fulcrum effect. In the present report, we aim at demonstrating the central role of robotic surgery for deep infiltrating endometriosis, with special emphasis in the ability to practice organ (rectal) preservation. A 45-year-old white female with a 4-month history of chronic pelvic pain, dyschezia, and dysmenorrhea, refractory to hormonal therapy was referred to our unit. MRI findings were diagnostic of deep infiltrating endometriosis (retrocervical and rectovaginal) extending to the anterior rectal serosal layer (partial-thickness rectal invasion). Using a fully robotic approach, appropriate dissection of the rectovaginal septum and of the extraperitoneal rectum followed by complete excision of the endometriotic rectal nodule with organ (rectal) preservation was undertaken. It is our belief that using a robotic approach, the potential to boost rectal preservation might be established. Moreover, it is possible that in many cases, a robotic operation may allow the surgeon to perform the intervention with greater accuracy and comfort. As a result, more patients with deep infiltrating endometriosis may benefit from rectal sparing procedures.